Diagnosis of knee injuries: comparison of the physical examination and magnetic resonance imaging with the findings from arthroscopy - Nilton Orlando Júnior; Marcos George de Souza Leão; Nelson Henrique Carvalho de Oliveira (Revista Brasileira de Ortopedia, 2015)
ABSTRACT OBJECTIVES: To ascertain the sensitivity, specificity, accuracy and concordance of the physical examination (PE) and magnetic resonance imaging (MRI) in comparison with arthroscopy, in diagnosing knee injuries. METHODS: Prospective study on 72 patients, with evaluation and comparison of PE, MRI and arthroscopic findings, to determine the concordance, accuracy, sensitivity and specificity. RESULTS: PE showed sensitivity of 75.00%, specificity of 62.50% and accuracy of 69.44% for medial meniscal (MM) lesions, while it showed sensitivity of 47.82%, specificity of 93.87% and accuracy of 79.16% for lateral meniscal (LM) lesions. For anterior cruciate ligament (ACL) injuries, PE showed sensitivity of 88.67%, specificity of 94.73% and accuracy of 90.27%. For MM lesions, MRI showed sensitivity of 92.50%, specificity of 62.50% and accuracy of 69.44%, while for LM injuries, it showed sensitivity of 65.00%, specificity of 88.46% and accuracy of 81.94%. For ACL injuries, MRI showed sensitivity of 86.79%, specificity of 73.68% and accuracy of 83.33%. For ACL injuries, the best concordance was with PE, while for MM and LM lesions, it was with MRI ( p < 0.001). CONCLUSIONS: Meniscal and ligament injuries can be diagnosed through careful physical examination, while requests for MRI are reserved for complex or doubtful cases. PE and MRI used together have high sensitivity for ACL and MM lesions, while for LM lesions the specificity is higher. Level of evidence II - Development of diagnostic criteria on consecutive patients (with universally applied reference "gold" standard).